Sleeve Gastrectomy as a Novel Procedure for Gastroparesis. Issue 8 (August 2021) - Alicuben, Evan T.; Samaan, Jamil S.; Houghton, Caitlin C.; Soffer, Edy; Lipham, John C.; Samakar, Kamran
Background: Laparoscopic sleeve gastrectomy (LSG) has recently been considered for the surgical management of refractory gastroparesis. Our study aims to determine the efficacy of LSG as a new treatment modality for gastroparesis. Methods: A multi-surgeon single institution retrospective chart review of patients who underwent LSG for refractory gastroparesis from September 2016-December 2017. Pre- and postoperative Patient Assessment of Upper Gastrointestinal Disorders-Symptoms Severity Index and/or Gastroparesis Cardinal Symptom Index (GCSI) questionnaires were reviewed. A telephone survey was conducted. Statistical analysis consisted of two-sample t test and utilized SAS v9.4. A P -value <.05 was considered significant. Results: There were 10 patients included and 80% were women with an average age of 43 years (24-63). Mean Body Mass Index was 24.5 (16.8-39.6), and median gastric emptying at 4 hours was 50% (30-85). Etiology of gastroparesis was 50% idiopathic, 40% diabetic, and 10% postsurgical. 80% of patients had previously undergone gastric electrical stimulator implantation, 20% pyloric botox injections, and 1 patient jejunostomy tube placement. One patient required conversion from laparoscopic to open secondary to adhesions. Median length of stay was 5 days (2-13), and median follow-up was 13.3 months. 90% of patients were tolerating a regular diet at longest follow-up with significant improvement in self-reported symptoms. GCSI scores were 33.6 preoperatively and 14.9 postoperatively ( P = .01). Discussion: Our study adds to the literature examining the role of LSG in the treatment of gastroparesis. LSG has favorable outcomes at short-term follow-up for patients with refractory gastroparesis.